2020
DOI: 10.3389/fnins.2020.00345
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Sensory Feedback in Upper-Limb Prostheses From the Perspective of Human Motor Control

Abstract: This manuscript reviews historical and recent studies that focus on supplementary sensory feedback for use in upper limb prostheses. It shows that the inability of many studies to speak to the issue of meaningful performance improvements in real-life scenarios is caused by the complexity of the interactions of supplementary sensory feedback with other types of feedback along with other portions of the motor control process. To do this, the present manuscript frames the question of supplementary feedback from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(166 citation statements)
references
References 220 publications
(291 reference statements)
2
140
0
Order By: Relevance
“…In this case, it would be relevant to compare the performance with and without tactile feedback to assess the added value of the subdermal interface. As reported in a recent review ( Sensinger and Dosen, 2020 ), both non-invasive and invasive approaches to restoring sensory feedback can improve performance and user experience, yet this is not a simple relation but depends on many factors. The functional test will allow comparing potential benefits to the challenges related to the application of the subdermal interface (e.g., minimal invasiveness).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, it would be relevant to compare the performance with and without tactile feedback to assess the added value of the subdermal interface. As reported in a recent review ( Sensinger and Dosen, 2020 ), both non-invasive and invasive approaches to restoring sensory feedback can improve performance and user experience, yet this is not a simple relation but depends on many factors. The functional test will allow comparing potential benefits to the challenges related to the application of the subdermal interface (e.g., minimal invasiveness).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that closing the loop can improve performance ( Clemente et al, 2016 ; Schiefer et al, 2016 ; Markovic et al, 2018 ; Shehata et al, 2018 ; Clemente et al, 2019 ; George et al, 2019 ; Petrini et al, 2019 ), compensate cognitive burden ( Risso et al, 2019 ; Valle et al, 2020 ), and facilitate embodiment ( Page et al, 2018 ; Valle et al, 2018a ; Rognini et al, 2019 ). Therefore, the development of sensory feedback for myoelectric prostheses is an important task that is in the focus of the present research efforts ( Sensinger and Dosen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…(D) Once the reconnection of the two ends of the injured nerve is achieved, these neurons will be able to reinnervate the former target tissue, divided into sensors and muscles; or in the case that the target tissue has been lost, the reconnection with bionic interfaces. (Micera et al, 2011;Zecca et al, 2017;Clemente et al, 2019;D'Anna et al, 2019;Sensinger and Dosen, 2020).…”
Section: The Need Of An Ordered and Differentiated Regeneration Of Sementioning
confidence: 99%
“…Proprioceptive information such as limb position or speed are communicated to the user indirectly using separate sensory channels including vibration [9]- [13] and audio [14]- [16] cues, among others [17]. However, although studies typically show improved limb control with sight of the prosthesis obscured, these benefits do not always translate to tasks where the prosthesis is visible [18] -some studies demonstrate improvement [19]- [22], while others show no change [22]- [25].…”
Section: Introductionmentioning
confidence: 99%